Isolation and identification of the microbial strains from the dental plaque in the patients with fixed dental appliances – preliminary study - Cristina Nicoleta MIHAI; Gabriel CIOCHINDA; Claudia Camelia BURCEA; Mihai BURLIBASA; Viorel Stefan PERIEANU; Madalina Violeta PERIEANU; Oana EFTENE; Iuliana BABIUC; Ruxandra STANESCU; Olivia POPOVICIU; Madalina MALITA; Radu COSTEA; et al. (Romanian Journal of Medical Practice, 2020)
Introduction. A special role in the occurrence of acute or chronic infections is the microbial biofilms, which contain several microbial species and which develop mainly on inert surfaces. Purpose. The objective of this research is to obtain scientific information on microbial biofilms relevant to human health, in order to identify and improve the prophylactic and therapeutic methods of the infections caused by them. Material and method. This research focuses on the study of the microbial plaque attached to the dental surfaces, from patients wearing fixed dental appliances. The study was performed on a number of 39 patients wearing fixed orthodontic appliances. Results and discussion. Several types of microbial strains have been identified – Burkholderia cepacia, Pseudomonas aeruginosa, Serratia liquefaciens, Enterobacter cloacae, Eikenella corodens, Lactobacillus sp., Bacteroides sp., Candida albicans etc. Conclusion. The identification of the microbial strains isolated from the dental plaque revealed a great diversity of the aerobic and aerobic facultative anaerobic microbial species, which supports the hypothesis of the nonspecific bacterial plaque, involved in the etiology of periodontal diseases.